Asian Prosperity and Entrepreneurs - EAA Editorial Office (Education About Asia, 2021)
The dramatic rise in prosperity for many millions of East Asians can, unlike miracles, be explained at its most basic level in two words: incentives and entrepreneurs. Governments in East Asia, beginning with Japan, understood and consistently provided incentives that created opportunities for large numbers of people to feed their families and otherwise prosper. Entrepreneurs—individuals with the talent, prescience, and audacity to take financial risks that resulted in successful national and international business ventures—constituted a vital force driving East Asia’s post-war economic rise, as well as India’s marked improvement in the late 1990s and the first two decades of the twenty-first century. The selections that follow all focus upon entrepreneurs and are useful for a wide range of academic disciplines including anthropology, economics, political science, world history, human geography, and leadership.
Keywords: Business; China; Economic History; Economics; Japan; Northeast Asia; Taiwan